Transformasi Makna Komunikasi Transendental Cak Nun Kepada Kiaikanjeng - Setiawan, Erik (Jurnal Komunikasi Islam, 2017)
Transcendental communication is often assumed as a exclusive form or pattern of communications, even though transcendental communications laden with human values inclusively. KiaiKanjeng is a group or arts community especially in music, which with unique deemed to have values in their transcendental communications and so far can still exist amid the mainstream of the music industry today. Research on Transformation of Meaning of Transcendental Communications Cak Nun to KiaiKanjeng is an attempt to formulate a transcendental communication to the ‘soft’ implementation area, so communication in transcendental area is not something complicated to understand. The method used for this study is a qualitative research with phenomenological methodology. The results obtained from this study is the transformation of meaning of the transcendental communication Cak Nun to KiaiKanjeng; understand, feel and believe that what is happening is part of the process from Journey by Allah. That transcendental for the sake of social action based on divining of KiaiKanjeng, implemented in their show image divine of Allah that has two basic demands that are sociological-horizontal and vertically-theological.